Implementasi Analisis Swot Pada Strategi Marketing Penerbit Buku Di Kota Medan - Azhari Akmal Tarigan; Yenni Samri Juliati; I Ismail (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2019)
The high level of competition in various business fields today demands the management of the company to improve the excellence of the products it has, in competition in the business world the company is required to find a special strategy to create Competitive advantage so that it can put its company in the position of market leader and always ahead so that always be the choice of consumers. Online digital collections such as E-Book and You Tube that are widely available on the internet make the world of book publishing increasingly competitive as well as the implementation of improper strategies can give a bad impact to publishing companies, there are persons that markets products that are not original (pirated books) are troubling the publishing world. For that, it is necessary to find out the Marketing strategy conducted by book publishers in Medan, to know what are the obstacles in implementing Marketing strategy conducted by book publishers in Medan City and finally to The effort to overcome the obstacles in implementing the Marketing strategy conducted by the publisher in Medan City. This article is with a qualitative descriptive approach by using SWOT analysis. The results of the research from SWOT analysis are S-O strategy with aggressive, i.e. (S2, O2) a book made from quality paper materials and quality content makes the library demand increase annually. (S1, O1) Direct selling that is done by campus company can increase profit and big profit due to higher education market. (S3, O3, O2) The company is working with a national bookstore that is likely to have a wide network and distributed on a national scale as well as many growing library requests annually.